KAJIAN ESTETIKA KURSI EKSPERIMENTAL - Hawari, Firman (Dimensi Interior, 2011)
Designing chairs in the 20Â th century was marked by the efforts to reduce dependency on nature while accelerating issues of the environment and also motivating people to explore their creativity wider. As an implementation of the above aims, several chairs were designed with attempts to explore new values, one of which was material exploration. These attempts include the emergence of new values on many kind of experiments such as the finishing, processing, structure, ergonomics, and which are eventually directed to the final chair form. This research uses the qualitative method of approach with emphasis on the aesthetic meaning and logic of the experimental chair. The aims include identifying the principles of designing experimental chairs through several analyses such as the analysis of experiments that had been done and the analysis of form and function. The research was also undertaken using the methods of description and comparison to analyze the aesthetic values of experimental chairs. Results revealed that the forms produced on experimental chairs were more to be impacted by the process of production elements like materials, color, structure, manufacturing, and finishing that eventually establishes new forms that are more unique and unusual than conventional chairs. The new forms seen on experimental chairs reflect more of contemporary and postmodern values. Contemporary values are represented by the visual uniqueness that relates to contemporary aesthetics while postmodern values were showed by the concept of universality inside it. It is hoped that the conclusions of this paper would determine the direction and orientation of experimental chair design so that it becomes a stimulus chair of deeper chair design development in the future